Some New Elements in Positioning Anchorage Area for Passenger Cruisers Near Port of Dubrovnik - Jelavić, Vedran; Kurtela, Željko; Brajović, Miloš (Promet - Traffic&Transportation, 2006)
There are several factors to be considered while creating anchoragearea for cruising ships. Mandatory elements includedin the analyses of the anchorage area are: security factor,aquatorium factor, ship factor, environmental pollution factor,anchorage occupancy factor and legal issues. Consideringmany specifics of the city of Dubrovnik and the surroundingarea some new principles had to be included in order to find themost convenient solution for the new anchorage area. Theseprinciples are proportionality, traditionality and diversity appliedto some aspects of cruisers and anchoring aquatorium.With such approach it was possible to position the optimal areafor anchoring near very sensitive old city of Dubrovnik and satisfyall the subjects included in that problem.